2020
DOI: 10.13080/z-a.2020.107.036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sowing date on bread wheat kernel quantitative and qualitative traits under Middle East climate conditions

Abstract: The current study explored the effects of six spring wheat (Triticum aestivum L.) cultivars, four sowing dates (early, timely, late and very late) and their interactions on quantitative and qualitative traits during two cropping years. A combined analysis of variance (ANOVA) indicated that the effect of sowing date was significant on kernel yield and filling period. The quality traits were not significantly affected by the sowing date. Interaction of sowing date × cultivar × year was significant for some quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Similarly, improved grain yields were attained under optimal sowing conditions by (Said et al, 2012;El-Areed et al, 2017;Ren et al, 2019;Sayed et al, 2021). Sasani et al (2020) found that negative effects of late sowing date on bread wheat performance through poor germination, which causes a decrease in growth of individual plants and reduces number of spike per plant under low temperatures when compared to recommended sowing date.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, improved grain yields were attained under optimal sowing conditions by (Said et al, 2012;El-Areed et al, 2017;Ren et al, 2019;Sayed et al, 2021). Sasani et al (2020) found that negative effects of late sowing date on bread wheat performance through poor germination, which causes a decrease in growth of individual plants and reduces number of spike per plant under low temperatures when compared to recommended sowing date.…”
Section: Discussionmentioning
confidence: 99%
“…Sowing after 30 th November led to decrease most of the studied traits in both seasons. Sasani et al (2020) indicated that negative effects of late planting on crop performance through poor germination, which causes reduction in growth of individual plants and reduces tiller production under low temperatures when compared to early planting. The interaction between wheat cultivars and sowing dates had a highly significant effect on all studied traits in both seasons (Table 6).…”
Section: Trait Means and Analysis Of Variancementioning
confidence: 99%
“…The analysis of variance for protein content indicated variance across all experimental factors and their interactions (Y × F, Y × S). In their studies, Kadar et al [57] and Sasani et al [59], concluded that the protein content was significantly influenced by both the year and the genotype. Furthermore, additional research has demonstrated that the protein content in spring wheat varies considerably depending on the wheat genotype and nitrogen dose [57,58,[60][61][62].…”
Section: Resultsmentioning
confidence: 99%